Desenvolvimento de metodologia de extração e determinação de ácido aminometilfosfônico e glifosato em água de abastecimento público - Delmonico, Eduardo Luiz (2013)
The use of pesticides in agriculture is one of the current problems that may result in contamination of both ground and surface water and groundwater. The use of these water for human and animal supply can result in serious health risks and, strict control to verify that these harmful compounds are eliminated during water treatment should be made. Considering the environmental importance and the increasing use of herbicides in Maringa region, in the present work methods for extraction and determination of glyphosate and aminomethylphosphonic acid using solid phase extraction, capillary electrophoresis and high performance liquid chromatography were developed. For solid phase extraction, anion exchange resin was used and elution was done with hydrochloric acid 50.0 mmol L-1, achieving recovery rates of 82.5-116.2% and 67.1-104.0% for AMPA and glyphosate respectively. For chromatographic determination the analytes were derivatized and the determination by HPLC was done by using a C18 column and a mobile phase consisting of phosphate buffer 0.20 mol L-1 at pH 3.0 and acetonitrile (85:15), the monitoring was done at 240 nm. The analysis was performed in 8 min with the same limit of detection and limit of quantification for AMPA and GLYP of 0.06 and 0.20 mg L-1, respectively. The method was applied to analysis of public water supply samples and were found the concentrations of 2.11 up to 2.85 μg L-1 for AMPA and 2.28 up to 3.27 μg L-1 for glyphosate. The developed method to determine the analytes by capillary zone electrophoresis used 2.00 mmol L-1 sodium borate buffer and 30 μmol L-1 fluorescein sodium salt at pH 9.0. The standard solutions and commercial herbicide samples were injected into the fused silica capillary under pressure 1.0 psi for 5 s and the analytes separation was conducted under a potential of 15.0 kV at 25.0 °C and monitoring at 520 nm by laser induced fluorescence. The analysis was done in 6 min and obtained limits of detection and limit of quantitation 0,97 3.20 mg L-1 for AMPA and glyphosate respectively. The method was adequate to analysis of commercial samples of herbicide and it was obtained the value of 496.0 ± 6.3 mg L-1